Need for Standardization During Cable Tensioning: An In Vitro Experimental Study on a Femoral Osteotomy Model - Birsel, Olgar; Koyuncu, Özgür; Eren, İlker and Günerbüyük, Caner and Bozdağ, Ergün and Sünbüloğlu, Emin and Kılıçoğlu, Önder (Cerrahpaşa Medical Journal, 2024)
Objective: The ideal tension on a cable is affected by several factors, and the tensioning process is a relatively complex procedure. Individual variations can occur during tensioning, and the strain applied by residents at different training levels has not been previously questioned. For this purpose, we investigated the variations in the peak tensions applied by orthopedic residents, using a cable fixation model created on sheep femur. Methods: The experiment was conducted on the distal diaphysis of a 1-year-old sheep femur. A cobalt chrome cable, tensioned with a strain-meter integrated tensioner, was utilized to stabilize a prosthetic stem. The minimum tension required for a stable fixation under 8 N/m torque was recorded. Strain measurements of 120 trials of 12 residents were recorded and compared to their experience level and to the measured optimal tension. Results: The mean tension required for a stable fixation was 550 ± 45 N. The overall measured tension load was 540.3 ± 262.9 N. The mean tension provided by the 12 residents were between 175.7 ± 33.7 N and 875.5 ± 222.9 N. A significant difference was found between their highest and the lowest values (P < .0001). The level of experience was not correlated with the mean tension applied (P = .89) or with the difference of the minimum and the maximum tension (P = .81). The intraclass correlation coefficient was calculated as 0.1361 (95% CI, 0.02338-0.4242). Conclusion: Our results suggest that the residents’ decisions for the cable strain are not consistent or predictable, with high variations from the optimal value, regardless of their experience level. Cite this article as: Birsel O, Koyuncu Ö, Eren İ, et al. Need for standardization during cable tensioning: An in vitro experimental study on a femoral osteotomy model. Cerrahpaşa Med J. 2024;48(2):125-128.